Eça de Queirós: 160 anos de nascimento - Gomes da Costa, Antonio (2006)
To recall Eça de Queirós's a hundred and sixty birth (1845), it is outstanding the constant presence of Brazil in his work and the quantity of admirers the portuguese writer, like no one else, achieved in Brazil.